THE COTRIBUTION OF UNIVERSIRTY AS AN AGENT OF DUAL EDUCATION SYSTEM (PSG) TO SMK STUDENT’S INDUSTRY PRACTICE (PRAKERIN) - Paul Igunda Machumu; Haris Anwar Syafrudie; Aji Prasetya Wibawa (Jurnal Pendidikan Sains, 2017)
Abstract: One of the newest and most well-known training patterns for developing students career in terms of skills and knowledge is Dual Education System. This gives an opportunity for the student to attend for the real practical work in the real environment where learning is the real task and activities which equip students with the required skills and knowledge. These tasks and activities are really done in industrial work practices areas where they provide the knowledge appropriate on the student’s field of expertise. One the industrial practices areas are Universities. A survey was conducted using a questionnaire consisting of eight aspects which include: the implementations of the industrial practices (Prakerin). Based on school and students preparation, the resemblance of material provided theoretically and practically, supervision and monitoring students activities, facilities in the industrial practices area, students creativity and initiative, cooperation, students’ discipline and attendance, students achievement and lastly student’s readiness on doing industrial practices (Prakerin).The survey results show that there is the effectiveness of dual education system program on vocational students’ industry practices (Prakerin) in Universities.Key Words: dual education system, industrial practices area/placeAbstrak: Salah satu pola pelatihan terbaru dan paling terkenal untuk mengembangkan karir siswa dalam hal keterampilan dan pengetahuan adalah Pendidikan Sistem Ganda. Hal ini memberi kesempatan bagi siswa untuk berada dalam kerja praktek nyata di lingkungan yang sebenarnya dimana pembelajaran adalah tugas dan aktivitas nyata yang membekali siswa dengan keterampilan dan pengetahuan yang dibutuhkan. Tugas-tugas dan kegiatan tersebut dilakukan di praktek kerja industri di mana mereka memberikan pengetahuan yang tepat di bidang keahlian siswa. Salah satu tempat praktik industrinya adalah Universitas. Sebuah survei dilakukan dengan menggunakan kuesioner yang terdiri dari delapan aspek yang meliputi: implementasi praktik industri (Prakerin). Berdasarkan persiapan sekolah dan siswa, kemiripan materi yang diberikan secara teoritis dan praktis, pengawasan dan monitoring kegiatan sis-wa, fasilitas pada tempat praktek industri, kreatifitas dan inisiatif siswa, kerjasama, disiplin dan kehadiran siswa, serta prestasi siswa dan yang terakhir adalah kesiapan siswa dalam melaksanakan praktek industri (Prakerin). Hasil survei dalam penelitian ini menunjukkan bahwa ada keefektifan program pendidikan sistem ganda pada praktik industri siswa SMK (Prakerin) di Perguruan Tinggi.Kata kunci: pendidikan sistem ganda, praktik kerja industri